2012
DOI: 10.1186/1472-6963-12-262
|View full text |Cite
|
Sign up to set email alerts
|

Triage vital signs predict in-hospital mortality among emergency department patients with acute poisoning: a case control study

Abstract: BackgroundTo document the relationship between triage vital signs and in-hospital mortality among emergency department (ED) patients with acute poisoning.MethodsPoisoning patients who admitted to our emergency department during the study period were enrolled. Patient’s demographic data were collected and odds ratios (OR) of triage vital signs to in-hospital mortality were assessed. Receiver operating characteristic curve was used to determine the proper cut-off value of vital signs that predict in-hospital mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
25
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 18 publications
7
25
1
1
Order By: Relevance
“…The present study showed that there was statistically significant difference between the discharged and died patients as regards blood pressure, incidence of shock, heart rate, respiratory rate and body temperature where hypotension, shock, bradycardia, bradypnea and fever observed more in died patients than discharged patients. This was similar to the results observed by Lee et al (2008) and Yu et al (2012) who mentioned that there were significant differences in heart rate, systolic blood pressure, respiratory rate and body temperature between survivors and non-survivors. Also, this was in agreement with Lee et al (2013) study in which there was significant association between the mortality and decrease in respiratory rate.…”
Section: Discussionsupporting
confidence: 91%
“…The present study showed that there was statistically significant difference between the discharged and died patients as regards blood pressure, incidence of shock, heart rate, respiratory rate and body temperature where hypotension, shock, bradycardia, bradypnea and fever observed more in died patients than discharged patients. This was similar to the results observed by Lee et al (2008) and Yu et al (2012) who mentioned that there were significant differences in heart rate, systolic blood pressure, respiratory rate and body temperature between survivors and non-survivors. Also, this was in agreement with Lee et al (2013) study in which there was significant association between the mortality and decrease in respiratory rate.…”
Section: Discussionsupporting
confidence: 91%
“…Again, the absence of a central point of entry and of a triage system for new patients may have contributed to inconsistencies in measurements or documentation. As vital signs are important markers of the severity of illness and have been shown to be reliable predictors of death following trauma and acute poisoning in low- and middle-income countries, these should be measured and documented in every patient 18 , 19 …”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27] However, very few studies have looked as triage parameters as the outcome predictors for poisoning cases in emergency or these were done for single agents. [28][29][30] Our study shows significant difference in triage findings (SPO2, AVPU scale and MAP) for mortality and no mortality groups (fig 1). Similar findings were noted for triage parameters like body temperature <36 or >37°C, p <0.01, systolic blood pressure <100 or >150 mmHg, p<0.01, heart rate <35 or >120 bpm, respiratory rate <16 or >20 per minute to predict mortality of acute poisoning cases in emergency.…”
mentioning
confidence: 99%
“…Similar findings were noted for triage parameters like body temperature <36 or >37°C, p <0.01, systolic blood pressure <100 or >150 mmHg, p<0.01, heart rate <35 or >120 bpm, respiratory rate <16 or >20 per minute to predict mortality of acute poisoning cases in emergency. 30 This highlights the need for a systematic triage especially in our country where there are resource constraints.…”
mentioning
confidence: 99%